Electroacupuncture Regularizes Gastric Contraction and Reduces Apoptosis of Interstitial Cells of Cajal in Diabetic Rats - Wang, Hongcai; Zhao, Kaile; Shi, Ning; Niu, Qiong; Liu, Chengxia; Chen, Yan (Frontiers in Physiology, 2021)
Background/Aims: Gastric dysmotility is a frequent complication among patients with diabetes mellitus. Electroacupuncture (EA) has been empirically used to relieve gastrointestinal symptoms. The aims of this study were to investigate the effects of EA on gastric contraction and the mechanisms of interstitial cells of Cajal (ICC) involved. Methods: Male Sprague-Dawley rats were randomized into the normal control, diabetes (DM), diabetic and sham EA (DM+SEA), diabetic and low-frequency EA (DM+LEA) and diabetic and high-frequency EA (DM+HEA) group. Diabetic models were established and then treated with EA for 8 weeks. Body weight and blood glucose were recorded every two weeks. The spontaneous contractions of distal gastric strips were analyzed. Immunostaining and RT-PCR were used to test the apoptotic ICC, IGF-1/IGF-1R and Nrf2/HO-1 pathways. Results: The body weight in the DM+LEA and DM+HEA group were increased compared with the DM group, though there was no effect on the blood glucose. The gastric contractions were obviously disordered in the DM group, but EA could regularize the contractions. The number of apoptotic ICC was dramatically increased in the DM group, but reduced with EA treatment. Meanwhile, IGF-1/IGF-1R pathway was verified to be significantly altered in diabetic rats. Nrf2/HO-1 pathway was not significantly increased in the DM group. EA with different frequencies efficiently improved the expression of IGF-1/IGF-1R signaling, and activated the Nrf2/HO-1 pathway. Conclusion: EA could improve gastric motility dysfunction and attenuate ICC apoptosis possibly through the regulation of IGF-1/IGF-1R and Nrf2/HO-1 pathways. EA may be a potential therapeutic method for diabetic gastric motility dysfunction.